Surgical Outcomes in Macular Telangiectasia Type 2-Related Macular Holes: A Report on Four Patients. (7th December 2020) - Ahmad, Kinza T.; Chacko, Joseph; Sallam, Ahmed B.; Warner, David B.; Uwaydat, Sami H.
Abstract : Introduction . The few published studies that exist on the surgical outcomes of full-thickness macular hole (FTMH) repair in Macular Telangiectasia (MacTel) Type 2 report poor rates of hole closure of around 30%. This study is the largest case series of patients with FTMH in MacTel Type 2 and describes an 80% hole closure rate. Purpose / Aim . To describe the outcomes of four patients who underwent surgery for FTMH associated with MacTel Type 2. Methods . A retrospective review of clinical, surgical, and imaging data of five eyes in four patients with MacTel Type 2 FTMH who underwent pars plana vitrectomy (PPV) with internal limiting membrane (ILM) peeling and 30% SF6 or 15% C3 F8 gas tamponade within 3-9 months of initial vision decline. Results . Visual acuity (VA) at the time of surgery ranged from 20/50 to 20/200. Successful hole closure was achieved in four out of five eyes, and final VA ranged from 20/20 to 20/40 at follow-up visits greater than 20 months postoperatively. The single eye that did not achieve hole closure had a final VA of 20/60. Conclusion . Our case series describes higher hole closure rates and better final VA than previously published reports for macular hole surgery in patients with MacTel Type 2 FTMH.